Government Programs to Tap Online User’s Potential and Allow Them to Use It for Digital Marketing and Become Digital Ambassadors - Younus, Muhammad; Mutiarin, Dyah (UUM Press, 2023)
The purpose of the study in this paper is to provide details regarding the initiatives and programs for utilizing the untapped potentials of the users present on different social media sites by training them or guiding them to use their energy in something which will bring good results for them and make them digital influencers. Researchers who are working effectively in this research field are utilizing the qualitative research method. The research data related to it was obtained from Amazon programs, blogs, social media, and e-commerce sites, and it is shared descriptively. The finding from this paper indicates that the creation of programs like this will undoubtedly benefit social media users and improve the way social media is currently used by most people. The way forward to make it possible, multiple hurdles need to be passed for successfully implementing this program. The paper will be limited to the extent to which the motive behind it is clearly described, then describe the possible ways for creating this program and how it will work, and lastly, what effect the initiative will have on the social media users and the e-commerce market.